The End of Disarmament and The Arms Races to Come - Lichterman, Andrew (Social justice, 2002)
Part of a special issue on global threats to security. The writers contend that an increasingly unilateral and aggressive U.S. foreign policy is eroding the network of security treaties that has helped to stem the spread of nuclear, chemical, and biological weapons, hence contributing to the creation of conditions that risk triggering new arms races. They discuss in detail the revelations of the January 2002 Nuclear Posture Review (NPR), which indicated that America intends to retain thousands of nuclear weapons for the foreseeable future. They argue that with the leading nuclear power proceeding to ignore its Nuclear Non-Proliferation Treaty (NPT) obligation to end arms racing and move toward nuclear disarmament, the (NPT) will be acutely undermined. Arguing that America should rethink its NPR and make good on its NPT commitments, they outline steps that the U.S. should take in the interest of real security.